Application of a standard risk assessment scheme to a North Africa contaminated site (Sfax, Tunisia) -Tier 1. (January 2021) - Pereira, Ruth; Bouguerra, Sirine; Lopes, Isabel; Santos, Bárbara; Marques, Catarina R.; Silva, Cátia; Mestiri, Amira; Frankenbach, Silja; Hentati, Olfa; Khadraoui, Moncef; Römbke, Jörg; Ksibi, Mohamed; et al.
Abstract: Phosphorus is a critical element to agriculture, consequently global phosphate rock demand will remain rising to feed a growing world population. The beneficiation of phosphorous ore gives rise to several tons of a waste by-product [phosphogypsum (PG)] which valorisation is limited, within other reasons, by the risks posed to environment and human health. Although threatening, the accumulation in stacks is the only procedure so far practiced by several countries as a means to get rid of this industrial externality. As part of a NATO Science for Peace Project (SfP 983311) this study describes the application of an environmental risk assessment (ERA) framework, to assess the risks posed by a PG stack to the surrounding soils, in Sfax, Republic of Tunisia. The ERA followed a weight of evidence approach, supported by two lines of evidence (LoE): the chemical (ChemLoE) and the ecotoxicological (EcotoxLoE). Integrated risks point for risk values greater than 0.5 in soils collected in PG stack surrounding area. Soil salinization, has likely contributed to the exacerbation of risks, as well as to the lack of consistency between both LoEs. This study highlights the need of rethinking the weight given to each LoE in ERA, in areas where soil salinization is a reality. Graphical abstract: Image 1 Highlights: Tier 1 of risk assessment framework may include only two lines of evidence (LoE). Soil salinity accounted for the lack of coherence between LoE. Different weights given to each LoE may overcome the confounding effect of salinity. Abstract : Depending on possible confounding factors the weight of different lines of evidence that account for a risk assessment framework must be balanced.